2015
DOI: 10.1016/j.seizure.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of five minutes compared to three minutes hyperventilation during electroencephalography

Abstract: 16% of seizures and 30% of interictal EEG abnormalities triggered by HV occurred during the last 2min of HV, suggesting the clinical usefulness of prolonged hyperventilation for 5min. The vast majority of patients (99%) who are able to hyperventilate for 3min can complete 5min HV, without additional adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 10 publications
(20 reference statements)
8
37
0
Order By: Relevance
“…We found five studies that quantified the success of voluntary hyperventilation for induction of PNES events (Table 4). Craciun et al aimed to test whether 5 min of hyperventilation increased the diagnostic yield of EEG for clinical events compared to 3 min of hyperventilation [31]. They found that ten out of 22 PNES patients (45.5%) had an event during the 5-min hyperventilation, while [33].…”
Section: Hyperventilation For Induction Of Pnesmentioning
confidence: 99%
“…We found five studies that quantified the success of voluntary hyperventilation for induction of PNES events (Table 4). Craciun et al aimed to test whether 5 min of hyperventilation increased the diagnostic yield of EEG for clinical events compared to 3 min of hyperventilation [31]. They found that ten out of 22 PNES patients (45.5%) had an event during the 5-min hyperventilation, while [33].…”
Section: Hyperventilation For Induction Of Pnesmentioning
confidence: 99%
“…They found that patients benefitted from prolonging HV from 3 to 5 minutes: 16% experienced seizures, and in 30% interictal epileptiform discharges were triggered by the extra 2 minutes of HV. 11 In our study, HV while sitting triggered absence seizures in 17 patients (85%). Four of these children did not experience a seizure during supine HV, rendering sitting HV essential for diagnosis (p = 0.031) in these four children.…”
Section: Discussionmentioning
confidence: 46%
“…If no significant EEG changes, outside of normal buildup, are noted during the routine three minutes of HV, and there is a strong suspicion of absence epilepsy, the protocol should be prolonged and/or repeated according to laboratory standards 9 22 , 31 If there is unexpected abnormal hypersynchronization activity during HV, the possibility of hypoglycaemia or other metabolic abnormalities or simply that the patient may not have stopped hyperventilating should be excluded 30 . The technologist should always write down an assessment of the quality of patient effort periodically throughout this procedure as well as in the technologist report 22…”
Section: Eeg Yieldmentioning
confidence: 99%